2017
DOI: 10.15544/jws.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heavy Metals Contamination on Spring Abundance of Aquatic Macro-Invertebrates Inhabiting Lake Timsah, Egypt

Abstract: Abstract. Lake Timsah, Egypt receives several kinds of pollutants coming from domestic sewage of unconnected areas adjoining the shore and possibly marine pollution. During the last decades heavy metals have become common contaminants of aquatic and wetland environments throughout the world because of human activity and technological development. Increasing attention has been given during the last decade to the protection of marine and freshwater aquatic environment against pollution, both nationally and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Comparing the previous studies of Timsah Lake water, (Saad El-Din and Gad El-Hak, 2017), found lower metal concentrations; (El-Shenawy, 2004) obtained lower Cu, Fe, and Mn levels but higher Ni levels; (Ibrahim and Abu El-Regal, 2014) recorded higher values of Cr;and (Saad El-Din et al, 2014) found a higher value of Co and Cr respectively than in the present study.…”
Section: Seasonal Variationssupporting
confidence: 49%
“…Comparing the previous studies of Timsah Lake water, (Saad El-Din and Gad El-Hak, 2017), found lower metal concentrations; (El-Shenawy, 2004) obtained lower Cu, Fe, and Mn levels but higher Ni levels; (Ibrahim and Abu El-Regal, 2014) recorded higher values of Cr;and (Saad El-Din et al, 2014) found a higher value of Co and Cr respectively than in the present study.…”
Section: Seasonal Variationssupporting
confidence: 49%
“…Arca noae is considered as a marine invertebrate that is abundant in Egypt coastal governorates such as Alexandria, Port-Said and also exists in some lakes such as El-Timsah lake (Saad El-Din and Gad El-Hak, 2017). Its cheap cost and its easiness in consuming it raw without the need of cooking makes Arca noae a suitable and nutritious meal for the low-income people.…”
Section: Introductionmentioning
confidence: 99%